2018
DOI: 10.32598/hdq.4.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Disaster Triage Knowledge of Nurses Personnel in Public Hospitals of Ilam

Abstract: Background: Educational planning and managing critical situations of accidents and disasters are among the most important issues. Triage, which means the classification of patients and injuries based on specific situations and needs, is one of the important tasks of hospitals at times of disasters. In this study, triage knowledge and practice of nurses working in hospitals affiliated to Ilam University of Medical Sciences are evaluated. Materials and Methods: This is a cross-sectional and analytic study conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…Moreover, the results from the present study reveal that the levels of triage knowledge of EMS personnel did not differ significantly based on age and work experience. This is consistent with the findings of Asgari et al (2018). However, this result contradicts the findings of Sedaghat et al , which might reflect the role of continuous education and training (Sedaghat et al , 2012).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, the results from the present study reveal that the levels of triage knowledge of EMS personnel did not differ significantly based on age and work experience. This is consistent with the findings of Asgari et al (2018). However, this result contradicts the findings of Sedaghat et al , which might reflect the role of continuous education and training (Sedaghat et al , 2012).…”
Section: Discussionsupporting
confidence: 88%
“…The findings from this study revealed that the average knowledge level on the START triage was lower than newly enrolled first-year medical students in the University of North Carolina in the United States as pointed out by Sapp et al (12.6 ± 19.58% out of 15) and nurses working in hospitals of Ilam University of Medical Sciences in Iran as pointed out by Asgari et al (10.4 ± 2.11 out of 15) (Sapp et al , 2010; Asgari et al , 2018). On the other hand, field EMS personnel in this study have a higher average knowledge level than EMS personnel in North Khuzestan in Iran, as shown in the study of Sedaghat et al (5.69 ± 2.5 out of 15) (Sedaghat et al , 2012).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…In addition, (Afaya et al, 2017;Aloyce et al, 2014), who found that many nurses were informed about triage, agreed with the current study's findings. Additionally, (Asgari et al, 2018) discovered that nurses had modest knowledge of triage.…”
Section: Discussionmentioning
confidence: 99%